SISTEM SPASIAL PERMUKIMAN MASYARAKAT DUSUN JIPANGAN YANG TERBANGUN OLEH KEGIATAN INDUSTRI KERAJINAN KIPAS BAMBU - , IKA ANINDITA, Prof. Ir. Sudaryono, M.Eng, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Small enterprises grow and develop by grouped in a certain location, which usually be called as sentra. Nearly all activities done by small entrepreneurs are happening in their homes or dwellings by using the existing space. While in a larger scope, production activities involve relation between houses in certain settlement spatial system (Untari, 2006). Sentra of bamboo-fan craft industry in Jipangan village is a domestic-based industrial region where 47 crafters live in their production houses, which distinguished by the specialized work of fan-crafting stages they perform. The connection between these houses forms certain production chain within the settlement in Jipangan village. People do activities in system of space in their settlement, whereas the development of certain activities encourages people to adapt with the space. This research aimed to understand how activities in bamboo-fan craft industry in Jipangan village can build a spatial system in local settlement space. This study is a research by inductive-qualitative method, using phenomenological paradigm. Data were collected by field observation and in-depth interview. There are 20 respondents chosen through purposive sampling and snowball sampling. Data were analyzed generally by grouping findings from the field (information units) to more general themes, and then induced to a concept or a local theory. Generally, this research concludes that the development of bamboo-fan craft in Jipangan village had encouraged interaction between settlement elements which formed new spaces, thus supporting production processes (micro and mezzo), sharing space for drying system, and production spatial network system. These elements interacted to form settlement spatial system, which create productive activities done by inhabitants. Settlements are processing and changing corresponds to the dynamics of activities within them. Therefore, settlements are not instantly built physical forms.